Chemical Characteristics of Lemon Cui (Citrus microcarpa) Infused Water with Various Combinations of Food Materials and Extraction Time - Handayani, Tri; Paneo, Yusran; Nurhayati, Nurhayati (Proceeding International Conference on Religion, Science and Education, 2025)
Lemon Cui (Citrus microcarpa) is an Indonesian citrus often found in Sulawesi, especially Gorontalo and North Sulawesi. The purpose of this study was to determine the chemical characteristics (vitamin C content, antioxidant activity, total phenol, and pH) of infused water made from Lemon Cui (Lcui) with various combinations of food materials and extraction time. The study was conducted using a completely randomized design (factorial) consisting of 2 factors, namely the combination of food materials (Lcui-dates, Lcui-cucumber, Lcui-watermelon) and extraction time (2, 4, 6, and 12 hours). Results showed that the chemical characteristics of infused water made from lemon cui in various combinations of food materials and extraction time respectively range from 10.83 – 39.9 mg/100g (vitamin C), 14.38 – 20.11% (antioxidant activity), 0.003 – 0.011% (total phenol), and pH 4.04 – 4.32. The combination of Lemon cui – watermelon and 4 hours extraction time gives the highest chemical characteristics of infused water, namely vitamin C content 37.4 mg/100g, antioxidant activity (RSA) 21.63%, total phenols 0.0112% and pH 4.15. In general, combining food materials and extraction time affected the levels of vitamin C, antioxidants, and total phenol-infused water made from lemon cui. This information can be used to develop drinks containing vitamin C and antioxidants made from local fruit.